FOXP3 Inhibits the Metastasis of Breast Cancer by Downregulating the Expression of MTA1 - Liu, Chenlin; Han, Jun; Li, Xiaoju; Huang, Tonglie; Gao, Yuan; Wang, Baolong; Zhang, Kuo; Wang, Shuning; Zhang, Wangqian; Li, Weina; Hao, Qiang; Li, Meng; et al. (Frontiers in Oncology, 2021)
Background: FOXP3, as a tumor suppressor gene, has a vital function in inhibiting the metastasis of breast cancer cells, but the mechanisms involved in the function of inhibiting metastasis have not been fully elucidated. This study intends to explore a new mechanism of FOXP3 in inhibiting breast cancer metastasis. Methods: Bioinformatic analysis was performed to identify potential downstream molecules of FOXP3. The function of FOXP3 in inhibiting MTA1 expression at the mRNA and protein levels was verified by real-time PCR and Western blot analysis. The interaction between FOXP3 and the MTA1 promoter was verified by transcriptomic experiments. In vitro and in vivo experiments were used to determine whether the regulation of MTA1 by FOXP3 affected the invasion and migration of breast cancer cells. Immunohistochemistry was adopted to explore the correlation between the expression levels of FOXP3 and MTA1 in breast cancer samples. Results: Bioinformatics-based sequencing suggested that MTA1 is a potential downstream molecule of FOXP3. FOXP3 downregulated the expression of MTA1 in breast cancer cells by directly inhibiting MTA1 promoter activity. Importantly, FOXP3's regulation of MTA1 affected the ability of breast cancer cells to invade and metastasize in vitro and in vivo. Moreover, clinical specimens showed a significant negative correlation between the expression levels of FOXP3 and MTA1 in breast cancer. Conclusion: We systematically explored a new mechanism of FOXP3 in the inhibition of breast cancer metastasis via the FOXP3-MTA1 pathway.